2012
DOI: 10.1590/s0034-70942012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito perioperatório do índice de massa corporal elevado no bloqueio do nervo periférico: uma análise de 528 bloqueios interescalênicos guiados por ultrassom

Abstract: Background and objectives: Obese patients can pose a unique perioperative anesthetic challenge, making regional anesthetic techniques an intriguing means of providing analgesia for this population. Ultrasound guidance has been touted recently as being beneficial for this population in which surface landmarks can become obscured. In this study, the effect of increased Body Mass Index (BMI) on ultrasound guided interscalene peripheral nerve blockade is investigated. Material and methods: This study is a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…34,42 Another group of patients who may not receive complete benefit from ISB includes those with obesity. In a study of 528 patients receiving ISB, Schroeder et al 44 found that those with an increased body mass index required longer times to complete the block and reported inferior pain control postoperatively. SSNB has been proposed as a safe and efficacious alternative to ISB for postoperative pain control following shoulder surgery.…”
Section: Discussionmentioning
confidence: 99%
“…34,42 Another group of patients who may not receive complete benefit from ISB includes those with obesity. In a study of 528 patients receiving ISB, Schroeder et al 44 found that those with an increased body mass index required longer times to complete the block and reported inferior pain control postoperatively. SSNB has been proposed as a safe and efficacious alternative to ISB for postoperative pain control following shoulder surgery.…”
Section: Discussionmentioning
confidence: 99%